The Experience of System of Collective Management Organizations of Copyright and Related Rights in Foreign Countries (Eurasian Journal of Research, Development and Innovation, 2023)
Developed systems of collective management of copyright began to be created from the middle of the 19th century. Within the framework of the subject, it was studied in detail how right holders enter into agreements with persons using works (objects of copyright and related rights) on their own behalf on the basis of powers granted by collective management organizations, as well as collection, distribution and payment of royalties to right holders. Attention is paid to some urgent problems related to the improvement of this institution, international standards for copyright protection and comparative legal analysis of national legislation, as well as the opinions of scientists from Uzbekistan and other different countries. Suggestions and recommendations were put forward of scientific and practical importance for national copyright law